Deletions in the Y-derived amelogenin gene fragment in the Indian population - Sahoo Sanghamitra; Kashyap VK; Sitalaximi T; Trivedi R (BMC, 2006)
Abstract Background Rare failures in amelogenin-based gender typing of individuals have been observed globally. In this study, we report the deletion of a large fragment of the amelogenin gene in 10 individuals out of 4,257 male samples analyzed from 104 different endogamous populations of India. Methods Samples were analyzed using commercial genetic profiling kits. Those that exhibited failures in amelogenin-based gender identification were further analyzed with published as well as newly designed primers to ascertain the nature and extent of mutation. Results The failure rate among Indian males was 0.23 %. Though the exact size and nature of the deletion (single point mutations at a number of positions or a single large deletion) could not be determined in the present study, it is inferred that the deletion spans a region downstream of the reverse primer-binding site of commercially available amelogenin primer sets. Deletions were conspicuously absent among the Mongoloid tribes of Northeast India, while both caste and tribal groups harbored these mutations, which was predominantly among the Y-chromosomes belonging to J2 lineage. Conclusion Our study indicates that the different amelogenin primer sets currently included in genetic profiling multiplex kits may result in erroneous interpretations due to mutations undetectable during routine testing. Further there are indications that these mutations could possibly be lineage-specific, inherited deletions.